2007
DOI: 10.1007/s11325-006-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia symptoms and their correlates among the elderly in geriatric homes in Alexandria, Egypt

Abstract: The prevalence of sleep complaints increases steadily with age. Studies investigating insomnia among elderly people living in geriatric homes, especially among Egyptians, are scarce. This study aimed to determine the prevalence of insomnia symptoms among the elderly living in geriatric homes in Alexandria and their correlates. A cross-sectional survey of a representative sample of elderly population of geriatric homes in Alexandria was implemented. A total of 177 persons aged 60 years or older participated. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
7
23
2
5
Order By: Relevance
“…This proposes that insomnia should be deliberated for an important public health issue for elderly people. This result is in agreement with previous findings (Reid, 2006;Makhlouf, 2007;Enomoto, et al, 2010, Sabry, 2010, Jaussent, 2011. However, other studies in urban localities in Egypt reported a much lower rate of insomnia down to 33.4% (Bakr, 2012;Saber, 2013 andShokry, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This proposes that insomnia should be deliberated for an important public health issue for elderly people. This result is in agreement with previous findings (Reid, 2006;Makhlouf, 2007;Enomoto, et al, 2010, Sabry, 2010, Jaussent, 2011. However, other studies in urban localities in Egypt reported a much lower rate of insomnia down to 33.4% (Bakr, 2012;Saber, 2013 andShokry, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…These findings come in agreement with some studies (Su, 2004;Tsou, 2013;Shokry, 2014). In contrast other studies reported significant association between increasing the age and sleeping quality and insomnia (Makhlouf, 2007;Wong, 2011;El Kady, 2012). However, Adetola et al (2014) found no association between age and insomnia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The largest number of complaints about sleep has traditionally been observed among women (14,17) . A study with 177 institutionalized aged individuals found a risk about four times greater than non-restorative sleep complaints for women than for men (18) . A more thorough assessment of possible differences between men and women of this study, considering variables such as age, length of institutionalization and others did not find any characteristic that would explain this finding.…”
Section: Sleep Quality As a Function Of Sociodemographic Characteristmentioning
confidence: 97%
“…Aged people are particularly susceptible to the disruption of life routines, leading to consequences usually deleterious on their biological rhythms, especially the sleep/ wake cycle. A study with institutionalized elderly showed that living for less than a year at the institution represented a risk two and a half times higher to complain of non-restorative sleep (18) . The present study did not include elderly individuals with less than one year in the institution, but the fact is that there are no studies that accompany the duration of the impact of institutionalization on sleep, thus permitting to speculate that it could extend beyond the first year, as suggested by these findings.…”
Section: Sleep Quality As a Function Of Sociodemographic Characteristmentioning
confidence: 99%